Application of a knowledge discovery model in the age of Big Data - Rabelo, Emerson; Campos, Fernando Celso de; Silva, Leandro Magno Correa da (Brazilian Journal of Production Engineering, 2021)
The ease and evolution of technological access has been responsible for the speed and volume with which data is produced. As a result, scenarios, opportunities and challenges arise that favor decision-making and help the product development process (PDP). Therefore, the present work developed the model called MDC-PDP (Knowledge Discovery Model in the Product Development Process), aiming to support the knowledge discovery in the product development process. To support the model, traditional methodologies associated with Big Data demands were used. To illustrate its application, this model was applied in the application domain of the fashion industry. The model showed that efforts made in the early understanding of the data, can contribute to the extracted data being less comple. Another evidence is the dissociation between volume and data value, as the data value is not tied to its volume. Finally, the MDC-PDP also contributed to obtaining useful and new knowledge in the development of fashion collections, making it possible to apply the model in other application domains.
Keywords: Product Development; Knowledge Discovery; Big Data; Social Network